O papel da gestão compartilhada na preservação da Área de Relevante Interesse Ecológico (ARIE) do Sítio Curió (Fortaleza, Ceará) - Souza, Larissa Maria de Oliveira (2025)
This study aims to analyze the Area of Relevant Ecological Interest (ARIE) of Sítio Curió, a conservation unit located in Fortaleza, investigating the partnership model between the environmental agency and a Civil Society Organization of Public Interest (OSCIP) that enabled its creation, the fulfillment of partnership agreement goals, and the socio-environmental impacts perceived by users. The methodology involved document analysis, literature review, field observations, and questionnaires applied to visitors of the unit. The research evaluated management, signage, environmental education, infrastructure maintenance, and community engagement. The results indicate that the ARIE plays an essential role as a space for leisure and social interaction, especially for residents of neighboring neighborhoods with low Human Development Index (HDI). Advances were noted in educational signage, trail opening, and the encouragement of public use of the area. However, limitations were found in infrastructure maintenance, the systematic provision of environmental education, engagement with the local community, and enforcement, particularly due to persistent irregular waste disposal and the absence of a management plan. Boundary demarcation issues hinder territorial control and dialogue with residents. Additionally, there is a lack of ongoing research promoted by management to support updated conservation actions. It is concluded that the environmental agency–OSCIP partnership model adopted is promising for urban environmental protection, provided it is strengthened by firm commitments, sustained investments, participatory management, and continuous educational activities. Expanding and consolidating successful initiatives can significantly enhance the socio-environmental benefits of the ARIE of Sítio Curió, contributing to a sustainable, just, and resilient city.